Application of ethyl cinnamate based optical tissue clearing and expansion microscopy combined with retrograde perfusion for 3D lung imaging - Sun, Quanchao; Picascia, Tiziana; Khan, Arif ul Maula; Brenna, Cinzia; Heuveline, Vincent; Schmaus, Anja; Sleeman, Jonathan P.; Gretz, Norbert (Experimental lung research, 2020)
3 D imaging of the lung is not a trivial undertaking as during preparation the lung may collapse. Also serial sections and scans followed by 3 D reconstruction may lead to artifacts. The present study aims to figure out the best way to perform 3 D imaging in lung research. We applied an optical tissue clearing (OTC) method, which uses ethyl cinnamate (ECi) as a fast, nontoxic and cheap clearing solvent, for 3 D imaging of retrograde perfused lungs by laser confocal fluorescence microscopy and light sheet fluorescence microscopy. We also introduced expansion microscopy (ExM), a cutting-edge technique, in 3 D imaging of lungs. We examined and compared the usefulness of these techniques for 3 D lung imaging. The ExM protocol was further extended to paraffin-embedded lung metastases blocks. The MHI148-PEI labeled lung vasculature was visualized by retrograde perfusion combined with trachea ligation and ECi based OTC. As compared with trans-cardiac perfusion, the retrograde perfusion results in a better maintenance of lung morphology. 3 D structure of alveoli, vascular branches and cilia in lung were revealed by immunofluorescence staining after ExM. 3 D distribution of microvasculature and neutrophil cells in 10 years old paraffin-embedded lung metastases were analyzed by ExM. The retrograde perfusion combined with trachea ligation technique could be applied in the lung research in mice. 3 D structure of lung vasculature can be visualized by MHI148-PEI perfusion and ECi based OTC in an efficient way. ExM and immunofluorescence staining protocol is highly recommended to perform 3 D imaging of fresh fixed lung as well as paraffin-embedded lung blocks.